The Polish Counterterrorism System and Hybrid Warfare Threats - Gasztold, Aleksandra (Terrorism and political violence, 2022)
This article examines the origins, structure and role of the Polish counterterrorism system, which is then set against the rising threat posed by state and non-state actors employing hybrid warfare tools. We demonstrate the usefulness of anti-terrorist regulations, not only in counteracting terrorist groups, but also in the thwarting of operations engaged in by various entities waging hybrid warfare. We argue that lessons learned from the international struggle against terrorism can contribute to the development of proper prescriptions that seek to tackle hybrid threats. Extensive anti-terror instruments and measures implemented since 2016 are among the key elements in the contemporary defense and security doctrine being pursued by Poland. However, while the new regulations have provided intelligence agencies with strong powers that markedly enhance their capabilities regarding the recognition of hybrid threats, the same flexible legal regulations, subject to broad interpretation, may also serve a partisan agenda, and thus endanger the rule of law.